The drawing of the three - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2003)
Elaborating at great length on Robert Browning's cryptic narrative poem "Childe Roland to the Dark Tower Came," the second volume of King's post-Armageddon epic fantasy presents the equally enigmatic quest of Roland, the world's last gunslinger, who moves through an apocalyptic wasteland toward the Dark Tower, "the linchpin that holds all of existence together." Roland enters three lives in the alternate world of New York City: junkie and drug runner Eddie Dean, schizophrenic heiress Odetta Holmes, and serial murder Jack Mort.